A Detailed Study of Glaucoma in Adults, Its Pathogenesis, Diagnosis and Management - Sarwade, Prakash Pralhad; Mishra, Madhav Kumar; Jyoti; Kaur, Harpreet; Latha, C. Madhavi; Sherief, S. Hameedullah; Gaisamudre (Sarwade), Kavita Narayan; Khongshei, Rapborlang; Natubhai, Parmar Hemantbhai (Journal for Research in Applied Sciences and Biotechnology, 2024)
As the second most prevalent cause of blindness in the world, after cataracts, glaucoma diagnosis and treatment are crucial topics for general physicians to know. Glaucomas can often be categorised based on three key factors: the extent to which the anterior chamber angle is open or closed, the intensity of the onset (acute or chronic), and the underlying cause (primary or secondary). Most cases of glaucoma are primary, indicating the absence of any comorbidities. Nevertheless, secondary glaucomas may arise from a range of visual illnesses as their root cause. Individuals who are susceptible to developing chronic glaucoma should undergo regular eye examinations in order to detect the condition at an early stage and prevent the progressive deterioration of vision that may occur prior to diagnosis. Glaucoma leads to impairments in both central and peripheral vision fields due to damage to the optic nerve and the retinal nerve fibre layer. All current treatments, including drugs, lasers, and procedures, aim to reduce intraocular pressure (IOP) because it is the only factor that can be changed and is crucial in the progression of the condition. Pharmacotherapy is the usual first-line treatment, although its effectiveness is constrained by noncompliance, adverse effects, and cost. While laser and surgical methods offer the ability to effectively lower intraocular pressure (IOP) for extended periods and at a lower cost compared to medicine, they come with increased risks during the process and a higher likelihood of treatment not being successful. Various modern minimally invasive glaucoma operations have replaced conventional incisional therapies because they offer improved safety and reduced efficacy decreases. While the long-term success of minimally invasive glaucoma surgeries still needs to be determined by large-scale randomised trials, these methods have greatly transformed the surgical treatment of glaucoma.